Psychophysiological stress response after a 6-week Mindful Self-Compassion training in psychiatric rehabilitation inpatients: a randomized post-test only study - Andorfer, Andrea; Kraler, Sabina; Kaufmann, Paul; Pollheimer, Ewald; Spah, Christoph; Fuchshuber, Jürgen; Rominger, Christian; Traunmüller, Claudia; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2023)
Objectives: Mindfulness-based interventions (including self-compassion interventions) are effective in improving stress management at psychological and physical levels. Mindful Self-Compassion (MSC) is a newly developed program particularly aimed at increasing selfcompassion. The main objective of this study was to determine whether the psychophysiological stress response during a social-evaluative speaking task differs in inpatients participating in the MSC or the Progressive Muscle Relaxation (PMR) program at the end of their 6-week psychiatric rehabilitation stay (i.e., post-test only design). Method: Data from 50 inpatients (25 MSC, 25 PMR, 35 female) aged 19 to 76 years (M = 47.22, SD = 12.44) were analyzed in terms of psychophysiological stress response. For this purpose, heart rate variability, heart rate, and blood pressure were assessed together with several psychometric variables: positive and negative affect (PANAS), subjective stress perception (Visual Analog Scale), self-compassion (Self-Compassion Scale), cognitive reappraisal and suppression (Emotion Regulation Questionnaire), psychological distress (Brief Symptom Inventory-18), and appraisal and rumination (selected items). Results: After correction for alpha inflation no differences in the psychophysiological stress response and psychometric parameters between the MSC and PMR group were found. Discussion: In general, our results indicate that MSC is not superior to PMR training. However, more research with clinical randomized controlled trials investigating larger samples are needed to further affirm these initial findings.